Integral varieties of a system of differential equations with a random right part in the Banach space - Kolomiets , V. G.; Melnikov , A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The concept of an integral manifold of a system of differential equations with a random right-hand side is introduced. The problem of the existence of an integral manifold of a certain class of differential equations in a Banach space and several of its properties are investigated.